PENGEMBANGAN BUKU PANDUAN LITERASI BAGI GURU SEKOLAH DASAR - Maxsel Koro; Taty R Koroh; Paulina Riwu Ga; Gerson Aloumoi (FKIP Universitas Citra Bangsa, 2022)
Literacy skills need to be possessed by every individual in order to compete in an increasingly fierce global competition. Therefore, it is necessary to pay special attention to schools in developing students' literacy skills. The purpose of this service is to develop literacy guidebooks for elementary school teachers to support the development of student literacy. The development is carried out by applying the Four-D model which includes Define, Design, Develop and Disseminate. Disseminate conducted limited to teachers of SD Inpres Bertingkat Perumnas 3 Kupang City. Expert tests were conducted on two expert lecturers. The validation results show that the literacy guidebook is valid and suitable for use by teachers. Keywords: Elementary School, Literacy, and Literacy Guide.